2023
DOI: 10.1109/tiv.2022.3140344
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Infrared Single-Pedestrian Tracking for Advanced Driver Assistance System

Abstract: Tracking algorithms with low computational complexity and reliable performance are important in developing advanced driver assistance systems (DAS). This paper proposes a method of single-pedestrian tracking using thermal infrared cameras to meet the needs of DAS operating in nighttime and lowvisibility conditions. The proposed algorithm uses the background-aware correlation filter (BACF) as the basic tracking framework. In order to address the problem that directly introducing the convolutional features leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The importance of nighttime target tracking research has been increasingly recognized, but the majority of previous studies have attempted to solve this issue by altering the data source. For example, complex sensors such as infrared cameras [18], low-light cameras [19], and event cameras [20] were used to acquire images. Some scholars have made efforts to solve the night tracking problem from the visible light perspective.…”
Section: Related Workmentioning
confidence: 99%
“…The importance of nighttime target tracking research has been increasingly recognized, but the majority of previous studies have attempted to solve this issue by altering the data source. For example, complex sensors such as infrared cameras [18], low-light cameras [19], and event cameras [20] were used to acquire images. Some scholars have made efforts to solve the night tracking problem from the visible light perspective.…”
Section: Related Workmentioning
confidence: 99%
“…However, compared with colour images taken by RGB sensors, TIR images have clear disadvantages, such as low resolution, low signal-to-noise ratio, lack of texture and colour information, and blurred edges. These shortcomings increase the difficulty of achieving autonomous image understanding in an ADAS [6]. Kukkala et al indicated that object detection is a major part of vision-based ADAS [7].…”
Section: Introductionmentioning
confidence: 99%